A Clinical Management of Pandu with Yashtimadhu Shamananga Snehapaana: A Case Study: Exploring the Efficacy of Yashtimadhu Ghritha in Managing Pandu Roga (Journal of Advances and Scholarly Researches in Allied Education, 2021)
As per Acharyas, Panduroga is a disease condition where aggravated Tridoshas predominantly Pitta Dosha affects Dhathus causing deterioration of Varna and Bala thereby suffering with Alparaktha, Alpamedas, Nissara, Indriyadourbhalya, leading to Twak Vaivarnyatha or Pandutha. In contemporary science, Pandu Lakshanas can be found similar to the symptoms of Anaemia, a medical condition caused due to decrease in the total amount of Red Blood Cells or haemoglobin in the blood. According to Global data epidemiologist analyzation- 2017, India has highest prevalence of iron deficiency anaemia at 39.86.Though there has been research in various system of medicine, this disease still remains as a challenge to the medical world. According to Charaka, Ghritha is Uttamasneha and possess the actions of Pitta-Anilahara, conducive to Rasadhathu, Shukradhathu, Ojas and indicated for Ksheena and Abala. On observing the Yogas suggested by Acharyas for Pandu Roga Chikitsa, a large number of them were Ghritha Yogas suggesting the ability of Ghrithas to deal with Panduroga. Yashtimadhu (Glycyrrhiza glabra), can be seen as one of the most common ingredient in many Panduroga Chikitsa Yogas. So the present case study is designed to know the individual efficacy of Yashtimadhu Ghritha as Shamanaga Snehapaana in the management of Panduroga and is found effective in managing Vatadhikya Panduroga